WASTE PRODUCT OF GROWING THE GENUS ECHINACEA (ECHINACEA MOENCH) AS PROMISING SOURCE OF BIOLOGICALLY ACTIVE SUBSTANCES - Шершова, С. В. (Scientific Progress & Innovations, 2013)
The experimental foundation bioconversion of waste product of growing (chaff), purple coneflower (Echinacea purpurea (L.) Moench.) and pale coneflower (Echinacea pallida (Nutt.) Nutt.) was to carried out. The high activity of extracts of coneflower chaff, which had growth-stimulating effect to the test culture, was proved. Found that the highest stimulating activity has the extract of chaff purple coneflowers: aqueous solution at concentrations of 0.01 %, alcohol-0.01 %-0.001 % and with increasing concentration of alcohol in the extracts decreased their activity. For the first time it has been shown that chaff of Echinacea contains specific proteins - lectins, and their activity in the waste product of pale coneflower significantly exceeded then activity in the waste product of purple coneflower. Technological schemes to get of lectins and extracts of biologically active substances from waste growing product (chaff), was worked out for their effective use.